Association of interleukin-6 gene polymorphism (rs1800796) with severity and functional status of osteoarthritis in elderly individuals. Issue 2 (October 2015) - Fernandes, Marcos T.P.; Fernandes, Karen B.P.; Marquez, Audrey S.; Cólus, Ilce M.S.; Souza, Marilesia F.; Santos, João Paulo M.; Poli-Frederico, Regina C.
Highlights: Individuals carrying the C allele of IL6 gene have lower susceptibility to osteoarthritis. The C allele of IL6 gene was associated with minor radiological impairment in hip and knee osteoarthritis. Patients with osteoarthritis with C allele of IL6 gene have better functional status according to WOMAC questionnaire. Individuals harboring GC or CC genotypes of IL6 gene have a reduction in IL-6 serum levels. Abstract: Osteoarthritis (OA) is the most prevalent disease of the musculoskeletal system and it has an important genetic component. Despite several reports have shown the involvement of pro-inflammatory cytokine such as interleukin-1β and TNF-α, the role of interleukin-6 ( IL-6 ) in osteoarthritis is still unclear. Thus, this study aimed to analyze the relationship between the single nucleotide polymorphism in the portion −572 of the promoter region of the IL6 gene (SNP −572G/C) with hip and knee OA in the elderly. In this case–control study, 257 physically independent elderly were recruited (case group: 92 individuals with osteoarthritis and control group: 165 individuals with no osteoarthritis). Blood samples were collected from patients for the DNA fragments extraction and amplification by real-time polymerase chain reaction (PCR) by TaqMan system for subsequent genotyping of IL6 gene. The degree of joint damage was assessed by radiographic classification based on the criteria of Kellgren and Lawrence. The functional status was evaluated by Lequesne and WOMAC questionnaires. It was observed that individuals carrying the C allele have lower susceptibility to osteoarthritis (OR = 0.51, 95% CI: 0.32–0.80, p  = 0.004) and less radiological impairment for both hip (Fisher–Freeman–Halton test = 4.2 and p  = 0.04) and knee joints (Fisher–Freeman–Halton test = 4.7 and p  = 0.03). Regarding functional status, individuals carrying the C allele has a lower degree of functional impairment assessed by WOMAC (Mann–Whitney test, p  = 0.04), although no difference was observed in the Lequesne questionnaire ( p  > 0.05). Additionally, it was observed a marked reduction in IL-6 serum levels in individuals with GC and CC genotypes when compared to individuals harboring GG genotype. In conclusion, the polymorphism −572G/C IL6 is a protective factor for the presence and severity of hip and knee osteoarthritis in the elderly. Further prospective studies with large sample size and methods (e.g. effect of this polymorphism on gene expression, haplotype analysis for IL-6 promoter polymorphism) are needed to validate this study findings.